Evaluasi Implementasi Sistem Manajemen Kesehatan dan Keselamatan Kerja di Rumah Sakit - Bambang Setiawan; Diana Vanda D. Doda; Erwin Kristanto (Universitas Sam Ratulangi, 2020)
Introduction:The implementation of Occupational Health and Safety (OHS) is an effort that aims to reduce workplace accidents and occupational diseases. A hospital is a place of work that has a high risk to the safety and health of human resources in the hospital, patients, families who accompany patients, visitors, and the hospital environment. Objective: This study aims to describe the implementation of OSH policies at Wolter Robert Monginsidi Hospital. Methods: This study uses qualitative research methods. The recruitment of informants in this study used purposive sampling with the number of participants as many as 5 people consisting of the Director, Chair of MFK, MFK Members, Head of Room (Nurses), and Cleaning Service. Data collection was obtained by participatory observation, in-depth interviews, and documentation. Results: This study found that policies related to OSH have been prepared and exist, but the implementation of OSH policies in this hospital has not been optimal. Hindrances in implementing OHS policies are 1. Insufficient sources of funds; 2. Lack of human resources; 3. Limitations of PPE; 4. Negligence of workers or lack of safety behavior. The supporting factors in the implementation of K3 policies are 1. The existence of socialization of OHS policies in hospitals; 2. engage staff for OSH training. The achievement of Hospital OHS policies such as the establishment of OHS management system and OHS program planning. The achievement that has not been optimal is the setting of standards for the implementation of the hospital OHS management, and monitoring and evaluation, as well as reviews, have not been carried out. Conclusion: The implementation of the K3RS management system at the Robert Wolter Mongisidi Hospital has not implemented optimally because the establishment of the hospital OHS management system has just been formed and has not been coordinated.